2019
DOI: 10.1101/841353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stimulus reliability automatically biases temporal integration of discrete perceptual targets

Abstract: Decision making is a ubiquitous cognitive process that determines choice behaviour. In recent years there has been increased interest in how information about multiple discrete sensory events are combined in support of single, integrated decisions. Previous studies have shown that integrative decision-making is biased in favour of more reliable stimuli. As reliability-weighted integration typically mimics statistically optimal integration, it remains unclear whether reliability biases are automatic or strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…where W reflects the decision weight for the trained and untrained motion direction, x reflects response error relative to the average motion direction on each trial (D°), and Y reflects the distance of the trained and untrained motion directions from the average motion direction on each trial (D°). To account for the circular nature of the data, both x and Y were expressed as complex numbers (i.e., as Cartesian coordinates) (Brouwer and Heeger, 2009;Rangelov et al, 2020).…”
Section: Statistical Tests and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…where W reflects the decision weight for the trained and untrained motion direction, x reflects response error relative to the average motion direction on each trial (D°), and Y reflects the distance of the trained and untrained motion directions from the average motion direction on each trial (D°). To account for the circular nature of the data, both x and Y were expressed as complex numbers (i.e., as Cartesian coordinates) (Brouwer and Heeger, 2009;Rangelov et al, 2020).…”
Section: Statistical Tests and Modelsmentioning
confidence: 99%
“…Studies of decision-making based on single stimuli have shown that factors, such as the rate of evidence accumulation, or the decision threshold, vary for different decision alternatives (Salzman et al, 1990;Gao et al, 2011;John-Saaltink et al, 2016). There is also evidence to suggest that integrative decisions are biased toward more reliable stimuli (Raposo et al, 2012;Brunton et al, 2013), even when this leads to suboptimal decisions (Rangelov et al, 2020). We set out to investigate the temporal dynamics of evidence accumulation during integrative decision-making by using an implicit neurofeedback protocol to unconsciously reward prioritized processing of one stimulus over another.…”
Section: Introductionmentioning
confidence: 99%